A New Interpretation of Geodynamic Context and Typology of Moroccan Anti-Atlas Silver Deposits - Amina, Wafik; Abderahmane, Ramdani; Nouaman, El Aouad; Mohamed, El Ghazali (European Scientific Journal, ESJ, 2017)
The argentiferous deposits in the Anti-Atlasic chain in Morocco are encased in the meta-sedimentary, volcanic-sedimentary and volcanic terrains of the Neoproterozoic, structured and schistosed during the Pan-African orogenesis. These deposits are associated with terminal Neoproterozoic rhyolites and granitoids. The deposits of Zgounder, Imiter and Bou Madine have similarities; Structurally are controlled and associated with faults; The source of the mineralization is generally magmatic or crustal. Precipitation of the mineralization would result from the mixing of mineralized fluids with meteoric waters or brine pools. The silver deposits in the Anti-Atlas are characterized by a number of criteria, which confirm their orogenic character. These deposits are associated with orogenic accretion events in relation to Pan-African orogenesis during the Neoproterozoic. Mineralization is syn- to post-peak metamorphism, controlled and associated faults, with veins that can have significant vertical extensions. The pressure gradients, and temperature metamorphism, indicating an orogenic environment, with metamorphic facies greenschist in general. These deposits can all be linked to an argentiferous mega-event during the Upper Neoproterozoic and thus define an argentiferous metallogenic province.